Effect of nasal oxygen supplementation during apnoea of intubation on arterial oxygen levels: A prospective randomised controlled trial - Nishant Sahay (Indian Journal of Anaesthesia, 2017)
Background and Aims: Apnoeic oxygenation during laryngoscopy has been emphasised in recent recommendations for airway management. We aimed to compare the effect of nasal oxygen supplementation on time for pulse oximeter oxygen saturation (SpO2) to fall from 100% to 92% (desaturation safety time), to assess the arterial oxygen partial pressures (PaO2) with and without nasal oxygen supplementation and the time for SpO2 to recover from 92% to 100% after initiation of ventilation. Methods: This is a prospective randomised placebo-controlled trial involving sixty patients, where nasal oxygen supplementation given at 10 L/min during apnoea of laryngoscopy in one group of patients (Group O2) was compared to no oxygen supplementation in other group (Group NoO2). Desaturation safety period and the PaO2just after intubation were compared. Time for SpO2 to increase to 100% after initiation of ventilation was also assessed. Demographic details were compared using the Chi-square and t-tests. Student's t-test for independent variables was used to compare means of data obtained. Results: Desaturation safety period at 415.46 ± 97.23 seconds in group O2versus 378.69 ± 89.31 seconds in group NoO2(P = 0.213) and PaO2(P = 0.952) and time to recovery of SpO2 (P = 0.058) were similar in both groups. Rise in arterial carbon dioxide secondary to apnoea was slower in oxygen supplementation group (P = 0.032). Conclusion: Apnoeic oxygen supplementation at 10 L/min flow by nasal prong did not significantly prolong the apnoea desaturation safety periods or the PaO2in our study.